MBCL-17. EPIDEMIOLOGY, TREATMENT AND OUTCOMES OF INFANT MEDULLOBLASTOMA: A SINGLE CENTRE STUDY IN SINGAPORE. Issue 2 (22nd June 2018) - Tan, Enrica; Pagaduan, Aubrey; Ng, Lee Ping; Low, Sharon
Abstract: INTRODUCTION: Historically, young children less than 3 years old with medulloblastoma have worse survival rates than older counterparts whose adjuvant therapy include craniospinal irradiation. Their poorer prognosis may be explained by frequent metastases and different biology. Desmoplastic histology has been associated with more favourable outcomes. MATERIALS AND METHODS: Retrospective analysis of 11 children less than 3 years of age diagnosed with medulloblastoma between 1997 to 2015 was conducted. Data on patient demographics, tumour characteristics, treatment and survival was obtained from Singapore Children's Cancer Registry and case records. RESULTS: Median age of diagnosis was 1.8 years (0.29 to 2.86). Male: female ratio was 2.7:1. Metastatic disease was found in 5 patients at diagnosis (45%). Gross total resection was achieved in 7 cases (64%). Histology subtyping showed 3 nodular/desmoplastic, 2 large cell/anaplastic, 2 classic and 2 not-otherwise specified, and two were unknown. Molecular subtyping via nanoString was performed on 7 available archival samples. One infant was too ill for any adjuvant therapy. Eight patients were treated with a baby brain chemotherapy strategy and 2 patients received intensive chemotherapy as per Headstart II protocol. There are 3 survivors, with a median follow-up of 18 years (2.8 - 19.8) and include the only two patients with localized nodular/desmoplastic medulloblastoma. They had been treated with a baby brain chemotherapy with no radiotherapy. CONCLUSION: Optimal treatment of infant medulloblastoma remains challenging. Nodular/desmoplastic histology and localized disease portend a better prognosis.